Surgical wounds healing by Secondary Intention-2 Trial: outcomes and learning from the internal pilot phase and main trial - Catherine Arundel; Sabeen Zahra; Ian Chetter; on behalf of the SWHSI-2 Trial Investigators; Site investigators (Pilot and Feasibility Studies)
Abstract Background Randomised controlled trials are the most rigorous way of investigating the effectiveness of intervention(s) in healthcare settings. During their conduct, trials often run into challenges which if not overcome can lead to significant research waste. Inclusion of a pilot phase provides a way to evaluate elements such as recruitment rate, site set-up and participant follow-up and to address any difficulties early in the trial. The number of trials including a pilot phase is increasing; however, findings are rarely shared in detail, meaning relevant information and learning may not benefit the wider research community. We aimed to report the learning from the SWHSI-2 internal pilot phase, to inform internal pilot trial design and conduct and to also share the subsequent learnings from the main trial phase. Methods The design and outcomes of the 6-month internal pilot phase were embedded within the surgical wounds healing by secondary intention trial. The internal pilot phase assessed site set-up, participant randomisation, intervention delivery and follow-up rates using a pre-specified grading. Details of the impact of the pilot phase on, and subsequent changes to, the main trial phase are also presented. We highlighted the challenges faced during the study and detail strategies that were included to minimise or mitigate these. Results The trial achieved satisfactory site set-up and intervention delivery levels; however, recruitment and follow-up rates were lower than anticipated. Approval was received from the funder to proceed to the main trial. Following the pilot phase, and continually during the main trial phase, processes and documentation were reviewed, revised and evaluated to mitigate challenges observed in relation to site engagement, participant recruitment and outcome data collection. Conclusion Inclusion of an internal pilot enabled early identification of recruitment and retention challenges with a comprehensive suite of interventions subsequently introduced to mitigate these. There was a successful main trial. The findings from this pilot phase add to the evidence base on the design and evaluation of internal pilot phases of a RCT. Future studies including an internal pilot phase should be encouraged to report their experiences for the benefit of others. Trial registration ISRCTN26277546. Prospectively registered 25 March 2019, https://www.isrctn.com/ISRCTN26277546